Rancang Bangun Sistem Informasi Perencanaan Dan Pengawasan Proses Produksi Pada CV. Setia Kawan - Rachman, Rizky; Setyawan, Henry Bambang; Arnandy, Didiet Anindita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV Setia Kawan is a company that manufactures hydraulic. The production process is based on customer orders received by the Marketing Section, and then forwarded to the Department of Planning. After the Planning Division began to plot the progress of production, raw material requirements plan, and plan workforce needs are still done manually, by way of making it on a piece of paper. The weakness of manual recording is sometimes an error in the listing, which can result in a long time.Production Planning and Control is the determination and the determination of production activities to be undertaken to achieve the objectives of the mill company, and oversee the implementation of the activities and results of the production process, so that what has been planned can be implemented and the expected objectives can be achieved.To improve the planning and supervision of the production process at CV Setia Kawan by making information systems planning and supervision of the production process.By using the Production Planning and Control, the planning and control of production processes at CV Setia Kawan can support the performance of the planning section has an important role in the production process.